2012
DOI: 10.2106/jbjs.k.01434
|View full text |Cite
|
Sign up to set email alerts
|

Early Initiation of Bisphosphonate Does Not Affect Healing and Outcomes of Volar Plate Fixation of Osteoporotic Distal Radial Fractures

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
66
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 33 publications
2
66
0
1
Order By: Relevance
“…Most of the studies found no adverse effect of bisphosphonate on fracture healing. Gong et al 23 with a similar study design to ours, reported that ALN administration two weeks following surgery using locking plate and screws did not affect radiological or clinical outcomes of fracture healing in osteoporotic patients. The incidence of osteoporosis in patients with fragility fractures of the distal radius is reported to range from 30% to 47%, [39][40][41] and several fragility fractures, including at the distal radius, occur when the BMD is in the osteopenic range.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Most of the studies found no adverse effect of bisphosphonate on fracture healing. Gong et al 23 with a similar study design to ours, reported that ALN administration two weeks following surgery using locking plate and screws did not affect radiological or clinical outcomes of fracture healing in osteoporotic patients. The incidence of osteoporosis in patients with fragility fractures of the distal radius is reported to range from 30% to 47%, [39][40][41] and several fragility fractures, including at the distal radius, occur when the BMD is in the osteopenic range.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies on the effect of bisphosphonate on fracture healing in humans have reported inconsistent results, [17][18][19][20][21][22][23] which may arise from differences in study design, primary outcome measures, the bisphosphonate used and fracture site studied. Most of the studies found no adverse effect of bisphosphonate on fracture healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an increased time of healing was noted with bisphosphonate use, but that was deemed not satisfactory enough to demonstrate a clinical significance. Gong et al [16] conducted a study in 2012 to determine the effect of early administration of bisphosphonate on the healing of osteoporotic distal radius fractures. This study focused on a randomized clinical trial to determine how safe it is for a patient who has an acute distal radius fracture to be administered bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%
“…After reset, although the structure can be supported by the palmar plate, the repair of the articular surface will still be affected by the wrist stress, especially in elderly patients with osteoporosis and those with unstable comminuted fractures involving the articular surface due to violent injury (Day and Daly, 2012;Padegimas and Osei, 2013). For patients with serious bone defects, postoperative autologous or artificial bone grafting could effectively restore the radial length and prevent the postoperative collapse of the articular surface (Ozer et al, 2011;Gong et al, 2012;Hegde et al, 2013).…”
Section: Discussionmentioning
confidence: 99%